On MQS regulation, innovation and market coverage - Emanuele Bacchiega; Luca Lambertini; Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
We revisit Maxwell's (1998) analysis to show that MQS regulation has no effects on the high-quality firm's incentive to adopt a more efficient technology in a vertically differentiated duopoly with full market coverage and convex costs of quality improvements which are independent of the scale of production.
Keywords: 330